MANOEL FERREIRA DE ARAUJO GUIMARÃES (1777-1838): FROM THE NAVY ROYAL ACADEMY TO THE ROYAL MILITARY ACADEMY OF RIO DE JANEIRO - Ribeiro Saraiva, Luis Manuel (2020)
The aim of this paper is to give an account of the life and work of Manoel Ferreira de Araujo Guimarães up to the eve of Brazil’s independence in 1821, the year of his retirement from the Royal Military Academy. We start with his studies in the Navy Royal Academy and then we analyze in particular detail his work both in the Royal Academy of Ensigns, first in Lisbon and later in Rio de Janeiro, and in the Royal Military Academy of Rio de Janeiro. His work as editor of A Gazeta do Rio de Janeiro (The Rio de Janeiro Gazette) and in O Patriota (The Patriot) and O Espelho (The Mirror), the latter two journals founded by Guimarães, will also be contextualized.